On resurrection - Albertus, Magnus, Saint, 1193?-1280 (Fathers of the church. Mediaeval continuation, 2020)
"Written in the 13th century, this work by St. Albert the Great explores the topic of resurrection both in terms of Biblical insights and in terms of classical philosophical concepts, especially those of Aristotle. This wide-ranging work discusses, among many other topics, the nature of the human soul, the relationship between the body and the soul, the nature of life after death, the resurrection of the body and incorruptibility of the body, natural and supernatural causes, the vision of God, and how and why the resurrection of Jesus Christ occurred. The original language is Latin"--